Microglia-Specific Expression of Olfml3 Is Directly Regulated by Transforming Growth Factor β1-Induced Smad2 Signaling - Neidert, Nicolas; von Ehr, Alexander; Zöller, Tanja; Spittau, Björn (Frontiers in Immunology, 2018)
Microglia maturation takes place during the postnatal weeks and is characterized by the establishment of a unique microglia-specific gene expression pattern. Tmem119, Fcrls, Hexb, and Olfml3 have been identified among these microglia-specific genes. TGFβ1 has been reported as a critical factor for microglia maturation and maintenance and active TGFβ signaling precedes the inductions of microglial gene expression. In the present study, we demonstrate Olfml3 expression in adult microglia and further provide evidence that TGFβ1 induces upregulation of Olfml3 expression in postnatal microglia. Using chromatin immunoprecipitation and microglia-specific silencing of TGFβ signaling in vitro and in vivo, we in clearly show that Olfml3 is a direct TGFβ1/Smad2 target gene. Together, our data underline the importance of TGFβ1 as a critical regulator of microglia functions and microglia maturation and further broaden our understanding of TGFβ1-mediated effects on the resident immune cells of the central nervous system.